2016
DOI: 10.12657/denbio.076.003
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between soil water and fertilizer on leaf photosynthesis and δ13C of Catalpa bungei seedlings

Abstract: Abstract:Our objective was to identify combinations of irrigation and fertiliser application that promoted the photosynthetic productivity and water use efficiency (WUE) of Catalpa bungei. Using response surface methodology based on a rotatable central composite design, we conducted a pot experiment with C. bungei clone 004-1 seedlings. The experiment quantified the effects of interactions between soil water content (W), nitrogen application rate (N), and phosphorus application rate (P) on leaf net photosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the equation, t 1 , t 2 , and t 3 represent the initial process (the beginning of the rapid growth of the leaves), the peak period (the peak period of leaf growth), and the end stage (the end period of the rapid growth of the leaves), respectively [24]. The leaf expansion rate (cm −2 •day −1 ) was for a single leaf area/peak period [25]. The leaf expansion rate in this paper was the relative leaf expansion rate in the peak period.…”
Section: Discussionmentioning
confidence: 99%
“…In the equation, t 1 , t 2 , and t 3 represent the initial process (the beginning of the rapid growth of the leaves), the peak period (the peak period of leaf growth), and the end stage (the end period of the rapid growth of the leaves), respectively [24]. The leaf expansion rate (cm −2 •day −1 ) was for a single leaf area/peak period [25]. The leaf expansion rate in this paper was the relative leaf expansion rate in the peak period.…”
Section: Discussionmentioning
confidence: 99%
“…C. globosum can improve the defense enzyme activity of plants under adversity stress and stimulate the expression of resistance-associated genes, thus inducing plant systemic resistance ( Yin, 2014 ; Cong et al, 2015 ; Zhang et al, 2016 ). Moreover, it has been reported that the application of C. globosum agents can significantly increase the content of organic matter, nitrate nitrogen, and ammonia nitrogen, and the activity of soil urease, sucrase, and alkaline phosphatase, as well as affect the distribution of bacterial communities in the soil, and increase the number and diversity of bacteria, thus promoting the growth of Catalpa bungei and Malus hupehensis seedlings ( Song et al, 2015 ; Li, 2019 ). Therefore, C. globosum exhibits great biocontrol potential in disease prevention and growth promotion of plants.…”
Section: Introductionmentioning
confidence: 99%